Inspired Leadership: Using Spiritual Principles to Guide Department Chair Work - Kathy A Gainor Ph.D. (Academic Chairpersons Conference Proceedings, 2019)
In this workshop, participants will explore six universal spiritual principles that can be useful in guiding one’s work as a department chair in a way that upholds that mission of the department and facilitates stress reduction and mental health of the chairperson. Case studies from the experiences of department chairs will be examined.
Keywords: Leadership; Spiritual principles; Virtues; Mental health; Stress reduction